PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA NIRWANA COFFEE SPACE BOJONGGEDE - Pratama, Muhammad Diki; Paludi, Salman (Universitas Nusa Cendana, 2024)
This study aims to determine the relationship between product quality, service quality, and promotion on purchasing decisions at Nirwana Coffee Space Bojonggede. The population in this study were consumers of Nirwana Coffee Space Bojonggede. This study involved 100 respondents who were collected using the distribution of questionnaires using accidental sampling techniques. Multiple linear regression analysis was used to determine the correlation between the variables studied by using SPSS 24 software. The results showed that product quality, service quality, and promotion had a significant effect on purchasing decisions at Nirwana Coffee Space Bojonggede. Furthermore, product quality, service quality, and promotion simultaneously influence purchase decisions. Keywords: Product Quality; Service Quality; Promotion; Purchasing Decision